2013
DOI: 10.1007/s10549-013-2665-0
|View full text |Cite
|
Sign up to set email alerts
|

HER3, p95HER2, and HER2 protein expression levels define multiple subtypes of HER2-positive metastatic breast cancer

Abstract: Trastuzumab is effective in the treatment of HER2/neu over-expressing breast cancer, but not all patients benefit from it. In vitro data suggest a role for HER3 in the initiation of signaling activity involving the AKT–mTOR pathway leading to trastuzumab insensitivity. We sought to investigate the potential of HER3 alone and in the context of p95HER2 (p95), a trastuzumab resistance marker, as biomarkers of trastuzumab escape. Using the VeraTag® assay platform, we developed a dual antibody proximity-based assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 30 publications
0
45
0
Order By: Relevance
“…Several other clinical studies have also shown that efficacy of monoclonal antibodies including rituximab, 37,38 alemtuzumab, 39 and trastuzumab 40,41 is partly dependent on target antigen expression. Importantly, it is unlikely that CD38 is a general prognostic factor in MM.…”
Section: Discussionmentioning
confidence: 94%
“…Several other clinical studies have also shown that efficacy of monoclonal antibodies including rituximab, 37,38 alemtuzumab, 39 and trastuzumab 40,41 is partly dependent on target antigen expression. Importantly, it is unlikely that CD38 is a general prognostic factor in MM.…”
Section: Discussionmentioning
confidence: 94%
“…The VeraTag reporter is conjugated to an antibody (anti-HER3 Mouse mAb Ab-6; Labvision, Fremont, CA, USA) that binds a distinct epitope of HER3, while biotin is conjugated to a second antibody (anti-HER3 Mouse mAb clone B9A11; Monogram Biosciences) that recognizes a different HER3 epitope [13]. …”
Section: Methodsmentioning
confidence: 99%
“…HER2-positive breast cancer subtypes may be defined by quantitative measurements of total HER3 (H3T), p95HER2 (p95), and total HER2 (H2T) [13]. Multiple analyses of the HER family pathway were performed in formalin-fixed, paraffin-embedded tissues using VeraTag technology.…”
Section: Introductionmentioning
confidence: 99%
“…Influence of HER3 expression on PFS has been shown to be especially relevant in HER2-positive MBC patients treated with trastuzumab, with a HR of 5.8 (p = 0.001) [12,35], but also in non-metastatic BC it has demonstrated a reduced PFS at 10 years (75.5 vs. 64.8 %; p = 0.001) in a cohort of 449 patients [14,36]. On the contrary, higher HER3 mRNA expression has been associated with better PFS in 740 MBC HER2-positive patients treated with trastuzumab plus docetaxel and/or pertuzumab (HR: 0.81; p = 0.0348) [15,16,37] (Tables 3, 4).…”
Section: Her3mentioning
confidence: 99%